Effects of Iodine Treatment on the Development of Eggs and Larvae of Rabbitfish (Siganus guttatus Bloch, 1787) - Huyen Kieu Thi; Tran, Vinh Phuong; Tran, Nguyen Ngoc; Ngo, Thi Huong Giang; Ho, Ngoc Tram Anh; Nguyen, Xuan Huy; Nguyen, Quang Linh (Jurnal Ilmiah Perikanan dan Kelautan, 2024)
Abstract Iodine is proven to be an effective disinfectant for fish eggs and is commonly used in a hatchery to improve hatching and survival rates. However, tolerance to iodine can vary in different fish species, and it is essential to determine the optimal concentration to ensure successful hatchery production. This study investigated the optimum concentration and exposure time to iodine during incubation to improve rabbitfish larvae's hatching and fertilization rate from 4/2022 – 8/2022 in Thua Thien Hue, Vietnam. The study consisted of two experiments: Experiment 1 focused on different iodine concentrations: 0 ppm (C1), 50 ppm (C2), 100 ppm (C3), and 150 ppm (C4). Experiment 2 explored three exposure times: 10 minutes (T1), 20 minutes (T2), and 30 minutes (T3) to increase the fertilization, hatching, and survival rates at five days post-hatching. Data were compiled, analyzed, and compared by ANOVA using SPSS ver. 22.0. The results showed that 100 ppm iodine concentration at 20 minutes of exposure resulted in the optimum hatching, fertilization, and survival rates of S. guttatus during artificial reproduction. In the future, integrated solutions in the use of iodine solution for egg treatment and natural food supplementation at the larval stage should be recommended to improve the efficiency in artificial hatchery production of Rabbitfish. Highlight Research The concentration and incubation time of rabbitfish (Siganus guttatus) eggs affect the production efficiency of fingerling fish. Iodine concentration of 100ppm for 20 minutes is the best to treat fish eggs before incubation. The fertilization rate of eggs, hatching rate, and survival rate of larva after 5 days of hatching when washing by iodine concentration of 100 ppm was 86.44 ±84%, 96.14 ± 1.05%, 58.65 ± 7.60% respectively.